(untitled) (Palíndromo, 2024)
Individuals, despite being visually and mediatically involved with their reality, know little about the breadth of the communicative and political power of these productions. We note, therefore, the emergence of other literacies within the scope of commitments of contemporary school education. That said, we aim, for this article, to make an incursion on the epistemological bases that elucidate what we understand by a Media-Visual Literacy in the school territory, appropriating, for that, the theoretical-conceptual perspectives of the compositions: Communication/Education, Cultural Studies and Human Rights. This is, therefore, a theoretical-reflective study, characterized, methodologically, as qualitative, documental and bibliographical. In conclusion, this intellective lineage points out that a school willing to take media as an object of its study is a school that alphabetizes individuals to question not only the truths formatted in words, but also the maxims, which, disguised as images, circulate amicably through the society under the prism of being incontestable representations of the “real”.